The dependence of the phases’ duration of buckwheat growing period on the environmental weather-climatic factors - Tryhub , O. V.; Liashenko , V. V. (Scientific Progress & Innovations, 2019)
The aim of the article is studying the duration of the growing period and its phases in contrasting environmental conditions concerning heat and moisture provision. Methods of the research. The analysis results of the selection and local material of 156 buckwheat varieties and forms of various origin from the National Collection of Ukraine during 2014–2018 in the Ustymivka experimental station of plant growing gave been presented. The research results. According to the results of the study, the early- and mid-ripening samples were distributed into subgroups according to the level of expressing indicators and the origin of the material. In addition to the level of expressing the trait, the variability of the duration of the main interphase periods in buckwheat and their dependence on weather and climatic conditions (according to the level of hydro-thermal coefficient) were determined and analyzed. For using in breeding researches, the samples from definite subgroups of ripening were recommended as basic and potentially more stable parent material, and also certain unique genotypes were identified as potential sources with genetically controlled duration of certain interphase vegetation periods. The need in such material is determined by the necessity of controlling the duration of plant growth and development phases to eliminate the influence or counteraction to unfavorable environmental factors and, as an example, the possibility of using various agro-technical methods for growing buckwheat (sowing time, varieties of different ripening time, etc.). The elements of scientific novelty. The duration of the vegetation period phases of buckwheat varieties and forms at different weather conditions with defining the hydro-thermal coefficient of each interphase plant growth and development period have been compared. The statistical parameters of stipulating the manifestation of the interphase periods’ duration indices in different buckwheat varieties concerning their ripening qualities were established. Practical importance. Potentially more suitable varieties for breeding and the local forms in the selection material with strictly controlled parameters of interphase vegetation periods’ duration were distinguished. The unique standard samples of buckwheat as to their characteristics were determined and recommended as a parent material with different vegetation duration, but rather considerable stability.